2020
DOI: 10.1002/hpja.398
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study exploring the dietary gatekeeper's food literacy and barriers to healthy eating in the home environment

Abstract: Socio-ecological models recognise the role of environments in shaping individual behaviour. 1,2 The home is one such environment that is a crucial setting for the development of food preferences 3,4 as well as influencing dietary behaviours of individuals, especially children. 5,6 While the sharing of meal related activities does occur in the home setting, most families possess a dietary gatekeeper who is primarily responsible for food purchasing and meal preparation for the family. 7,8 Dietary gatekeepers inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Food consumption within families is ultimately the product of interactions and negotiations between family members [46,47]. For greatest impact, efforts to improve food literacy and enhance skills and behaviours necessary to select and prepare healthy foods should target both men and women [47][48][49]. Family meals should be an educational tool for the acquisition of healthy eating habits, which will have an impact on nutritional behavior of all family members.…”
Section: Variablesmentioning
confidence: 99%
“…Food consumption within families is ultimately the product of interactions and negotiations between family members [46,47]. For greatest impact, efforts to improve food literacy and enhance skills and behaviours necessary to select and prepare healthy foods should target both men and women [47][48][49]. Family meals should be an educational tool for the acquisition of healthy eating habits, which will have an impact on nutritional behavior of all family members.…”
Section: Variablesmentioning
confidence: 99%
“…They were satisfied with their current behaviour or found it too difficult to change their habits (e.g., due to financial or logistic challenges or a lack of knowledge). These motivational, financial, and practical barriers have previously been described in other research on parental perceptions regarding children's dietary and PA behaviours [29][30][31][32]. Globally, three key factors necessary for behavioural change initiated by parents could be identified: (1) awareness of one's behaviour, (2) willingness to change, and (3) ability to change (including e.g., financial and practical abilities and parental food literacy).…”
Section: Discussionmentioning
confidence: 78%
“…Studies exploring the dietary gatekeeper's food literacy and its influence on the family's dietary outcomes are beginning to emerge, suggesting that it can help overcome challenges to healthy eating in the home environment (Perry et al., 2017; Wijayaratne et al., 2020). However, research has not yet identified how parents, particularly the dietary gatekeeper, share their knowledge of the four domains that comprise food literacy with others in the household.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Studies exploring the dietary gatekeeper's food literacy and its influence on the family's dietary outcomes are beginning to emerge, suggesting that it can help overcome challenges to healthy eating in the home environment (Perry et al, 2017;Wijayaratne et al, 2020).…”
Section: Food Literacymentioning
confidence: 99%